PRIVATE SCHOOL DIGITAL MARKETING DEVELOPMENT STRATEGY IN THE GLOBAL ERA (HIGH SCHOOL TAKHASSUS STUDY AL-QUR'AN BONANG DEMAK, ROUDHOTUT THOLIBIN HIGH SCHOOL WEDUNG DEMAK) ACADEMIC YEAR 2021/2022 - Zuhri; Sugiyo; A. Dardiri Hasyim (LPPM STAI DARUSSALAM LAMPUNG, 2022)
The formulation of the problem from the research, how is the marketing strategy in private schools, and how private schools face global competition. The purpose of this study is to analyze the marketing strategy of private schools, and to analyze private schools in the face of global competition. This research is a qualitative research, namely by photographing the condition of the school as it is, expressed in sentences, carried out in the field, to obtain materials and data by conducting interviews, observations, surveys, and documenting from principals, teachers, students, and parents. The results of this study prove, Takhassus al-Qur,an High School uses a digital marketing strategy, has increased students (in 2020/2021 received 130 and in 2021/2022 as many as 176 students), Roudhotut Tholibin High School, using conventional marketing strategies the number of students decreased, (year 2020/2021 got 26 students and in 2021/2022 as many as 24 students). This research is a reference for other private schools, digital marketing strategies have a positive impact on increasing the number of students in private schools, in the face of global competition.